Annual report 2013 - (:unkn) unknown (Publications Office of the European Union, 2014)
Cedefop's annual report is intended as a presentational and accountability tool which can help stakeholders and the general public to understand Cedefop's priorities and specific objectives, its main output and outcomes of its work. Information on each project is presented in a standard format, to make it easier to monitor and review projects' implementation. The issue 2013 gives an overview of Cedefop's key achievements in 2013. The second part monitors Cedefop's performance and monitors the implementation of the work programme 2013 by medium-term priority, actvity and project. (BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; I 1.5 Internationale Organisationen & Institutionen; I 2.2 Europa; CEDEFOP; Berufsbildungsforschung; EU-Bildungspolitik; Europäische Union; 2013